Program promosi kesehatan dalam upaya mencegah pernikahan dini - Asnuddin Asnuddin; Andi Palla; Wilda Rezki Pratiwi (Holistik Jurnal Kesehatan, 2021)
The knowledge of early marriage practices and the health impacts among adolescent in a health promotion program Background: Adolescence is a period of human life that is very strategic, important and has a broad impact on subsequent developments.Marriage at an early age is prone to reproductive health problems and is prone to stress. Health education media such as videos can be used as a tool in providing health education. The use of video media in providing health education is considered very appropriate to convey health messages to the public, especially among adolescents.Purpose: To determine the effect of the knowledge of early marriage practices and the health impacts among adolescent in a health promotion programMethod: Quantitative research with "Quasi Experiment" design with two Group Pretest-Posttest Design approach. Sampling using purposive sampling, the sample in this study were teenage students, with a total population and sample of 94 participants who were divided into two groups, namely groups with online media whatsapp and zoom with 47 participants and groups with offline media face-to-face 47 participants. For the measurement of knowledge using 20 questions with 3 categories, namely Good score 29-40, Enough score 24-28, Less score 0-23. Where the lowest score is 0 and the highest score is 40. The results of the analysis used the T test with a significance level of = 0.05 which was carried out with the help of the SPSS computer program.Results: The study show by nonparametric test using the Wilcoxon test, it was found that the value of p = 0.000, because the value of p = 0.000 <0.05 (α).Conclusion: Based on the research results, it can be concluded that there is a significant influence between health promotion and online media in preventing early marriage.Keywords: The knowledge; Early marriage practices; Health impacts; Adolescent; Health promotion programPendahuluan: Masa remaja adalah periode kehidupan manusia yang sangat strategis, penting dan berdampak luas bagi perkembangan berikutnya. Pernikahan di usia dini rentan terhadap masalah kesehatan reproduksi serta mudah mengalami stress. Media pendidikan kesehatan seperti video dapat digunakan sebagai alat bantu dalam memberikan pendidikan kesehatan. Penggunaan media video dalam memberikan pendidikan kesehatan dirasa sangat tepat untuk menyampaikan pesan kesehatan kepada masyarakat, terutama pada kalangan Remaja.Tujuan: untuk mengetahui pengaruh promosi kesehatan dengan terhadap kejadian pernikahan dini.Metode: Penelitian kuantitatif dengan desain “Quasi Experiment” dengan pendekatan Two Group Pretest-Posttest Design. Pengambilan sampel menggunakan purposive sampling, sampel dalam penelitian ini yaitu remaja siswa/siswi, dengan jumlah populasi dan sampel 94 partisipan yang dibagi dalam dua kelompok yaitu kelompok dengan media online whatsapp dan zoom dengan 47 partisipan dan kelompok dengan media offline tatap muka 47 partisipan. Untuk pengukuran pengetahuan menggunakan 20 pertanyaan dengan 3 kategori yaitu Baik skor 29-40, Cukup skor 24-28, Kurang skor 0-23. Dimana skor terendah 0 dan skor tertinngi 40. Hasil analisis menggunakan uji T dengan tingkat kemaknaan α = 0,05 yang dilakukan dengan bantuan program computer SPSSHasil: Dari hasil nonparametric test dengan menggunakan uji Wilcoxon didapatkan nilai p=0,000, oleh karena nilai p=0.000<0.05 (α).Simpulan: Berdasarkan hasil penelitian dapat di simpulkan ada pengaruh yang signifikan antara promosi kesehatan dengan media online dalam mencegah pernikahan dini .